2013
DOI: 10.1261/rna.041178.113
|View full text |Cite
|
Sign up to set email alerts
|

Probing N6-methyladenosine RNA modification status at single nucleotide resolution in mRNA and long noncoding RNA

Abstract: N 6 -methyladenosine (m 6 A) is the most abundant modification in mammalian mRNA and long noncoding RNA (lncRNA). Recent discoveries of two m 6 A demethylases and cell-type and cell-state-dependent m 6 A patterns indicate that m 6 A modifications are highly dynamic and likely play important biological roles for RNA akin to DNA methylation or histone modification. Proposed functions for m 6 A modification include mRNA splicing, export, stability, and immune tolerance; but m 6 A studies have been hindered by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
501
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 468 publications
(531 citation statements)
references
References 23 publications
24
501
0
6
Order By: Relevance
“…By comparing cDNA A-CLIP/IP (the A marked in red). SCARLET (site-specific cleavage and radioactive labeling followed by ligation-assisted extraction and thin-layer chromatography) is by Liu et al (2013) ) (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…By comparing cDNA A-CLIP/IP (the A marked in red). SCARLET (site-specific cleavage and radioactive labeling followed by ligation-assisted extraction and thin-layer chromatography) is by Liu et al (2013) ) (Fig. 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, this means that only a subset of Ψ's have been identified here. We used the evolutionary conservation of Ψ's in rRNA to validate our approach using tachyzoite rRNA; we further attempted to validate the Ψ's identified with CMCT using SCARLET (Liu et al 2013) and were able to do this for some of the highly conserved sites in the very abundant rRNA, but the amount of material we could generate for the mRNAs was not sufficient to use this method to validate Ψ's in this latter class of RNA (data not shown). Among the false negatives will be those that do not meet our Ψ criteria due to a relatively low level of pseudouridylation of a position in the total cellular pool of that transcript.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative density curve demonstrating that meRIP-seq peaks containing the 206 SPs exhibit significantly higher enrichment scores than those from remaining probes (P < 8.06 × 10 −7 , one-sided Wilcoxon rank-sum test) using previously generated MeRIPseq data. example, using a method known as SCARLET (for, site-specific cleavage and radioactive-labeling followed by ligationassociated extraction and thin-layer chromatography) to detect m 6 A on a specific RNA, Liu et al (2013) reported that the m 6 A fraction at different sites varies from 6% to 80%. Highly enriched m 6 A sites detected in our study likely play a functional role in regulating RNA activities.…”
Section: Discussionmentioning
confidence: 99%